Candidate chemosensory genes identified from the greater wax moth, Galleria mellonella, through a transcriptomic analysis - Hong-Xia Zhao (Nature Portfolio, 2019)
Abstract The greater wax moth, Galleria mellonella Linnaeus (Lepidoptera: Galleriinae), is a ubiquitous pest of the honeybee, and poses a serious threat to the global honeybee industry. G. mellonella pheromone system is unusual compared to other lepidopterans and provides a unique olfactory model for pheromone perception. To better understand the olfactory mechanisms in G. mellonella, we conducted a transcriptomic analysis on the antennae of both male and female adults of G. mellonella using high-throughput sequencing and annotated gene families potentially involved in chemoreception. We annotated 46 unigenes coding for odorant receptors, 25 for ionotropic receptors, two for sensory neuron membrane proteins, 22 for odorant binding proteins and 20 for chemosensory proteins. Expressed primarily in antennae were all the 46 odorant receptor unigenes, nine of the 14 ionotropic receptor unigenes, and two of the 22 unigenes coding for odorant binding proteins, suggesting their putative roles in olfaction. The expression of some of the identified unigenes were sex-specific, suggesting that they may have important functions in the reproductive behavior of the insect. Identification of the candidate unigenes and initial analyses on their expression profiles should facilitate functional studies in the future on chemoreception mechanisms in this species and related lepidopteran moths.